2009
DOI: 10.2174/1874091x00903010055
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exercise on L-Arginine Nitric Oxide Pathway in Chronic Heart Failure

Abstract: Chronic heart failure (CHF) is a pathological state with high morbidity and mortality and the full understanding of its genesis remain to be elucidated. In this syndrome, a cascade of neurohormonal and hemodynamic mechanisms, as well as inflammatory mediators, are activated to improve the impaired cardiac function. Clinical and experimental observations have shown that CHF is associated with a generalized disturbance in endothelium-dependent vasodilation, which may contribute to the progression of ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 126 publications
2
11
0
Order By: Relevance
“…So, we confirmed the assumption that long-term training induces increase in NO bioavailability, whilst training cessations, i. e. physical inactivity, have negative effect – it leads to reversible changes and preclude the increase in NO bioavailability. That is in accordance with studies that showed that physically active people have greater basal NO production than sedentary population [27-29], as well as that exercise induces increase in basal NO production [30-32], especially in sedentary [33] and people with some kind of endothelial dysfunction [34-37]. However, it should be emphasized that these exercise-induced changes in NO bioavailabilty are transitory and can be lost during inactivity period [32].…”
Section: Resultssupporting
confidence: 89%
“…So, we confirmed the assumption that long-term training induces increase in NO bioavailability, whilst training cessations, i. e. physical inactivity, have negative effect – it leads to reversible changes and preclude the increase in NO bioavailability. That is in accordance with studies that showed that physically active people have greater basal NO production than sedentary population [27-29], as well as that exercise induces increase in basal NO production [30-32], especially in sedentary [33] and people with some kind of endothelial dysfunction [34-37]. However, it should be emphasized that these exercise-induced changes in NO bioavailabilty are transitory and can be lost during inactivity period [32].…”
Section: Resultssupporting
confidence: 89%
“…It is in accordance with numerous previous studies that showed that regular physical activity increases the bioavailibity of NO (Jungersten et al 1997;Kingwell et al 1997;Lewis et al 1999;Maeda et al 2001;Maiorana et al 2003;Mendes-Ribeiro et al 2009) and that physically active people have greater basal NO production compared with a sedentary population (Poveda et al 1997;Green et al 2004;Banfi et al 2006). Studies that investigated the effects of acute exercise on NO production yielded various results.…”
Section: Discussionsupporting
confidence: 91%
“…In the progression of heart failure NO may therefore mediate either essential vasodilation or cell death, via its toxic effects. 21,22 In healthy dogs plasma NOx levels correlate with NT-proANP concentrations and increases with age. 15 Indices of increased tissue activity have been reported in the mitral valves in dogs with MMVD, 23 and signs of endothelial dysfunction have been observed in dogs with MMVD through necropsy material, 24,25 by peripheral blood flow measurements, 26,27 and through analysis of plasma cGMP or precursors 28 and end-products 29 to NO.…”
Section: Introductionmentioning
confidence: 99%